ムセン LAN ヲ モチイタ GPSデータ エンカク カイシュウ システム ノ カイハツ - 土井, 浩一郎; ドイ, コウイチロウ; 青山, 雄一; アオヤマ, ユウイチ; 船木, 實; フナキ, ミノル; 大園, 伸吾; オオソノ, シンゴ; 早河, 秀章; ハヤカワ, ヒデアキ; Doi, Koichiro; Aoyama, Yuichi; et al. (2012)
P(論文) 無線LANを利用した2周波GPSデータ遠隔回収システムを開発した.このシステムは,GPSロガーとデータ送信装置からなる地上観測装置とデータ回収装置で構成され,コマンド送受信にはZigBee通信(2.4 GHz, 250 Kbps)を, GPSデータの送受信には無線LAN通信(2.4 GHz, 54 Mbps)を使用する.GPSロガーで収録された1秒サンプリングデータから毎日作成される30秒サンプリングデータファイルが送信される. これまで,(1)地上でのデータ回収試験,(2) 小型無人飛行機によるデータ回収試験,(3) 昭和基地・西の浦での実データ回収試験を実施した.(1) では,最大400 m 程度の距離で全データを回収でき,(2) では約250 m 以下の高さで飛行する飛行機により約24.5 MB のデータを回収できた.(3) では,10 分以内に約23.5 MB のGPS ブイデータの回収に成功しており,観測を止めることなくデータ回収が可能となった. A remote retrieval system, using a wireless LAN, was developed to retrieve dual-frequency GPS data. The system consists of a ground observation unit (comprising a dual-frequency GPS logger and a data transmission unit) and a data retrieval unit. In this system, we use the ZigBee communication protocol to transmit control commands (2.4 GHz, 250 Kbps) and a wireless LAN communication to transmit GPS data (2.4 GHz, 54 Mbps). Data of every 30 seconds to transmit to the data retrieval unit are re-sampled from 1-second data at 00 UT each day. We conducted three data-transmission tests with the system: (1) a ground data retrieval test, (2) a data retrieval test from the atmosphere of a few hundred meters high using a small unmanned aircraft, and (3) actual GPS-data retrieval tests from a GPS buoy deployed on sea ice at Nisi-no-ura Cove, Syowa Station, Antarctica. In test (1), we successfully received all the data from the ground observation unit when situated at distances of less than 400 m from the data retrieval unit. In test (2), we obtained approximately 24.5 MB of data from the aircraft at heights of less than 250 m. In test (3), we obtained approximately 23.5 MB of data from the GPS buoy within 10 minutes. The proposed system has the advantage of enabling continuous measurements without aborting the measurement at the data retrievals. departmental bulletin paper